2022
DOI: 10.1128/spectrum.02697-21
|View full text |Cite
|
Sign up to set email alerts
|

The Linker Region Promotes Activity and Binding Efficiency of Modular LPMO towards Polymeric Substrate

Abstract: The polysaccharide-disintegrating carbohydrate-active enzymes (CAZymes) are often found with multimodular architecture, where the catalytic domain is connected to an accessory CBM domain with the help of a flexible linker region. So far, the linker has been understood merely as a flexible spacer between the two domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…However, a small portion of the protein band remained in the precipitant lane, suggesting that the linker unexpectedly retains some substrate binding affinity. Although linkers are generally considered as flexible spacers between two domains, some studies have demonstrated that linkers can contribute to polysaccharide binding ( 36 ), aligning with our observed results.
Figure 2 Substrate binding and activity of Mt LPMO9G and its truncated forms .
…”
Section: Resultssupporting
confidence: 91%
“…However, a small portion of the protein band remained in the precipitant lane, suggesting that the linker unexpectedly retains some substrate binding affinity. Although linkers are generally considered as flexible spacers between two domains, some studies have demonstrated that linkers can contribute to polysaccharide binding ( 36 ), aligning with our observed results.
Figure 2 Substrate binding and activity of Mt LPMO9G and its truncated forms .
…”
Section: Resultssupporting
confidence: 91%
“…Srivastava et al recently investigated the role of the linker region of fungal Bc LPMO9C ( Table 1 ) focusing on its effect on catalytic performance and thermostability. The authors generated three linker truncation variants, where shortening of the linker seemingly resulted in lower cellulose-binding affinity [ 48 ].…”
Section: Linkers In Lpmosmentioning
confidence: 99%
“…Previous studies have indicated that the linker length and flexibility play an important role in the activities of some cellulases, such as BsCel5A from Bacillus subtilis (Ruiz et al, 2016) and PoCel6A from Penicillium oxalicum (Gao et al, 2015). The linker region promotes enzyme activity and binding efficiency of LPMO towards polymeric substrate (Srivastava et al, 2022). In addition, Sonan et al (2007) have reported that the linker region plays a key role in the cold adaptation of the a cellulase from an Antarctic bacterium.…”
Section: Discussionmentioning
confidence: 99%